Sustainable Road Construction Techniques for Community Development - Mohamad, Dadang (Global Writing Academica Researching and Publishing, 2023)
The adoption of sustainable road construction techniques is crucial for promoting community development and achieving long-term environmental benefits. This study explores various sustainable construction methods, such as the use of recycled materials, energy-efficient processes, and eco-friendly designs, and examines their impact on community development. Utilizing a literature review approach, the research synthesizes findings from existing studies on sustainable road projects and integrates qualitative insights from key stakeholders, including engineers, policymakers, and local residents. The findings reveal that sustainable road construction not only enhances environmental sustainability by reducing carbon emissions and resource consumption but also supports socio-economic development by improving access to services, creating job opportunities, and fostering social cohesion. Furthermore, the study identifies key challenges in implementing these techniques, such as higher initial costs and the need for specialized knowledge and training. The results underscore the importance of integrated planning and community involvement in overcoming these barriers and maximizing the benefits of sustainable road construction. This paper provides practical recommendations for policymakers and practitioners aiming to incorporate sustainability principles into road infrastructure projects, ultimately contributing to resilient and thriving communities.